Phytochemical Composition, and Antioxidant Activity of Stingless Bee (Heterotrigona Itama) Propolis for Wound Healing Potentials - Mayusef Sukmana; Swandari Paramita; Yadi Yasir; Sri Wahyuningsih; Idris Mandang; Iwan Muhammad Ramdan; Endang Sawitri; Daniel Tarigan (Griya Eka Sejahtera, 2026)
Background: Propolis from stingless bees Heterotrigona itama(H.itama) is a promising natural product with diverse biomedical applications. However, its bioactivity and antioxidant for wound healing remain poorly understood. This study aimed to evaluate phytochemical profile, and antioxidant activity of H. itama propolis collected from land forest in Kalimantan, Indonesia.Methods: Qualitative phytochemical screening was performed to identify secondary metabolites, and antioxidant capacity was assessed using the DPPH radical scavenging assay with ascorbic acid as a reference standard. The result of the phytochemical content and antioxidant activity will be compared with the literature study on wound healing.Results: Phytochemical tests showed the presence of flavonoids, saponins, tannins, phenolics, triterpenoids, terpenoids, and DPPH assay revealed antioxidant activity with an IC₅₀ value of 159.91 ppm compared to 2.71 ppm for ascorbic acid.Conclusion: H. itama propolis biologically active, demonstrating antioxidant potential linked to its phenolic and flavonoid content. These findings support that phytochemical content and antioxidant activity are potentials for wound healing.